The effectiveness of support services for Aboriginal and Torres Strait Island communities : interim report - Australia. Parliament. House of Representatives. Standing Committee on Aboriginal Affairs (Canberra : Australian Govt. Pub. Service, 1988)
Defines support service, effectiveness; conflicts in policies, practices at Commonwealth, State, local levels; conclusions; future directions.
At head of title: The Parliament of the Commonwealth of Australia.
AGPS cat. no. 8816469.
Some copies with Parliamentary paper stamp on verso t.p.
Bibliography: p. 19.
Also available online
Keywords: Aboriginal Australians -- Services for; Torres Strait Islanders -- Services for; Aboriginal Australians -- Social conditions; Torres Strait Islanders -- Social conditions; Government policy - Commonwealth; Government policy - Self determination - 1985-1992.; Australia